Fitting Alpha-Skew Distributions to Insurance Data - Leinwander, Aaron (My University, 2015)
In this study, we investigated applications of alpha-skew distributions to insurance claims data and compared their performance to standard models such as the normal and skew-normal distributions.
Color poster with text and graphs.
Keywords: Alpha-skew-normal distribution; Insurance data; Posters